Hintan : a journey in steel - Frewer, Richard; Tan, Hin L., 1958- (London : Black Dog Pub., 2010)
'Hintan: A Journey in Steel provides an insight into the practice of Hin Tan and his impressive career as an architect and as the principal Director of Hintan Associates. The book charters Hin Tan's influence as an architectural, airport and interior designer, following his work from startling his practice in 2000 until his latest projects, resulting in the first major work on this internationally renowned company. Establishing and leading Hintan Associates has given Hin Tan the opportunity to explore his relationship with airport design, a major theme running throughout his work. This includes work on Tirana, Kuala Lumpur and Roschino International Airports, all of which are illustrated within the book. Other major projects featured in this volume include Kongelige Teater, (Denmark), Tenaga Nasional Berhad Mosque, (Malaysia), Port of Mina Salman, (Bahrain), corporate Offices for the Port of Tanjung Pelepas and MAERSK Line.' -- Book jacket.
The making of an architect -- Ideas explored through projects -- Architectural design -- Airport design -- Interior design.
Includes bibliographical references.
Keywords: Tan, Hin L., -- 1958-; Architects -- Malaysia; Architecture -- Designs and plans; Airports -- Designs and plans; Interior decoration